Assessing the impacts of cytostatic drugs on freshwater biota - Monteiro, B. R. (2021)
Cytostatic drugs are a class of pharmaceuticals that have been increasingly used for cancer treatment. After being metabolized these drugs are excreted mainly via urine, reaching wastewater treatment plants, that do not always possess the proper means to effectively eliminate them, meaning they continuously enter the environment, possibly reaching surface and drinking waters. Since most anticancer drugs possess carcinogenic, teratogenic, genotoxic, and mutagenic properties, they pose a potential risk to environmental and human health. In this context, the present work aimed at assessing the ecotoxicity of three commonly used cytostatic drugs (cyclophosphamide-CYP, mycophenolate mofetil-MMF, mycophenolic acid-MPA) on freshwater species representing different trophic levels and functional groups: the microalga Raphidocelis subcapitata, the rotifer Brachionus calyciflorus, and the fish Danio rerio. The following endpoints were monitored for each species: yield and population growth rate for the alga after an exposure of 72h; mortality for the rotifer after an exposure of 24h; and mortality, malformations, and hatching for the fish after an exposure of 96h. Overall, MMF and MPA proved to be the most toxic compounds, with LC50 values of 0.046 and 1.41 mg/L for zebrafish assays, respectively, against an LC50 of 1305.6 mg/L for CYP. Similar results were obtained for R. subcapitata. For the rotifer, LC50 values could not be computed for MMF and MPA, since at the highest tested concentration (40 and 30 mg/L, respectively (close to the solubility limit of the compounds)) no mortality was observed. Though an LC50 of 6397 mg/L for CYP was determined. Based on these results, the predicted no-effect concentrations (PNEC) were derived for each compound to calculate the risk quotient. The environmental predicted or measured concentrations in superficial waters were retrieved from the literature. In general, CYP revealed a low risk for freshwater biota (RQ = 0.003), while MMF and MPA presented RQ values above 1 (RQ=3.0 and 4.1, respectively), indicating a high risk to freshwater organisms.